Effect of Time Token Model Containing Science Literacy on Students’ Learning Competencies at Senior High School in Batusangkar - Ummul Haq Z; Rahmawati Darussyamsu; Sa'adiatul fuadiyah; Syamsurizal syamsurizal (Universitas Negeri Padang, 2020)
Research on the problems that exist in Batusangkar 1 Senior High School, student learning competencies are still low. The efforts that can be done are to implement a time learning model that contains scientific literacy. The purpose of this study was to determine the effect of the time token model with scientific literacy on the learning competency of students' in Batusangkar 1 Senior High School. This type of research was experimental research with a randomized control group posttest only design. The population in this study were all class X MIPA Batusangkar 1 senior high school registered in the 2018/2019. Sampling was done using Purposive Sampling techniques. X MIPA 2 as the experimental class and X MIPA 1 as the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. Based on the results of the study using the t-test it can be concluded that the knowledge competencies of students t count 3.41> t table 1.67, the attitudes competency t count 5.95> t table 1.67, and the skills competency tcount 2.34 > t table 1.67. it shows that the hypothesis was accepted. So, the application of the time token model with scientific literacy can improve the competency of knowledge, attitudes, and skills of class X students of senior high school 1 Batusangkar